2018
DOI: 10.12659/ajcr.911624
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Pulmonary Mucoepidermoid Carcinoma in an 81-Year-Old Male

Abstract: Patient: Male, 83Final Diagnosis: Pulmonary mucoepidermoid carcinomaSymptoms: Chronic coughMedication:—Clinical Procedure: —Specialty: PulmonologyObjective:Rare diseaseBackground:Lung mucoepidermoid carcinoma is a form of non-small cell lung carcinoma that originates from the submucosal glands of the tracheobronchial tree; it is rare and causes 0.1% to 0.2% of lung malignancies. In this article, we report on an occurrence of this condition in an 81-year-old male, which is rare occurrence in this age group. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Less commonly, MEC presents with pain, facial numbness, paralysis, or respiratory symptoms such as dyspnea, cough, chest pain, and mucopurulent expectoration depending on location, size, extension, and compressive effects over underlying nerves. Pulmonary MEC usually present as endobronchial tumors with a polypoid growth, obstructing the bronchial lumen [3,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Less commonly, MEC presents with pain, facial numbness, paralysis, or respiratory symptoms such as dyspnea, cough, chest pain, and mucopurulent expectoration depending on location, size, extension, and compressive effects over underlying nerves. Pulmonary MEC usually present as endobronchial tumors with a polypoid growth, obstructing the bronchial lumen [3,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Akciğerde MEK, trakeobronşiyal submukozal bezlerden köken alan, oldukça nadir görülen bir tümördür. Tüm primer akciğer kanserlerinin %0,1-0,2'sini oluşturur (10). MEK her yaş grubunda görülebilmekle birlikte, sıklıkla, 45-70 yaşları arasında, her iki cinste eşit oranda görülmektedir (11).…”
Section: Discussionunclassified
“…15 The patient also reported that several colleagues suffered from the Balkan syndrome, a complex chronic illness characterised by disorders mainly affecting the haematopoietic system and associated with exposure to DU, chemicals, desert dust, biological agents and vaccines. 16 This syndrome has also been observed in soldiers deployed in Bosnia-Herzegovina and Kosovo in the late 1990s. The latter were exposed to North Atlantic Treaty Organization antitank missiles and bombs containing DU that might be linked to the development of neoplasms.…”
Section: Global Healthmentioning
confidence: 90%